2008
DOI: 10.2215/cjn.01400308
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation Is Not Associated with Regression of Left Ventricular Hypertrophy

Abstract: Background and objectives: Patients with end-stage renal failure (ESRD) have an increased risk of premature cardiovascular (CV) disease. Left ventricular hypertrophy is an independent risk factor for CV events and death in ESRD. Renal transplantation has been associated with reduction in CV risk and echocardiographic regression of left ventricular hypertrophy. However, echocardiography overestimates LV mass in ESRD patients. Cardiac magnetic resonance (CMR) provides more detailed, volume-independent, measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 17 publications
4
78
4
Order By: Relevance
“…Above all, the current study results displayed different significance levels compared with the results from other studies28 29 because we demonstrated that LVH persistently regressed during the 5-year post-transplant period and because graft survival was considerably less frequent in the patients with persistent LVH in the fifth post-transplant year than in those experiencing LVH regression or in those with no pretransplant LVH. This correlation remained significant after adjusting for other risk factors, including the use of medications disrupting allograft function (diuretics, RAS blockers and others), and was confirmed by ROC curve analysis, revealing strong discriminating power.…”
Section: Discussioncontrasting
confidence: 93%
“…Above all, the current study results displayed different significance levels compared with the results from other studies28 29 because we demonstrated that LVH persistently regressed during the 5-year post-transplant period and because graft survival was considerably less frequent in the patients with persistent LVH in the fifth post-transplant year than in those experiencing LVH regression or in those with no pretransplant LVH. This correlation remained significant after adjusting for other risk factors, including the use of medications disrupting allograft function (diuretics, RAS blockers and others), and was confirmed by ROC curve analysis, revealing strong discriminating power.…”
Section: Discussioncontrasting
confidence: 93%
“…Patel et al (23) used cardiac magnetic resonance imaging to study LV parameters and found no significant difference in LV mass index, LV end-diastolic or end-systolic volumes, or LVEF over time between patients who underwent renal transplantation and those who remained on dialysis. Our finding that listing status (whether transplanted or not by the end of follow-up) and severe impairment of LV function were both significant in multivariate analysis suggests that severe LV impairment pretransplantation confers an increased mortality risk even after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Following renal transplant, LVH has been shown to improve when measured using echocardiography [93] , this LVH regression was seen until two years following transplantation, after which the effect plateaued [94] . However, a recent report using cardiac MRI, which is accepted as the "gold standard" to assess the LV, found that there was no difference in the LV measurements in RTRs compared to those who remained on dialysis [95] . There have been several studies which have inves tigated potential interventions to improve LVH.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%